Specialized palliative home care in Sweden with special respect to the development in sparsely populated areas - Axelsson, Bertil (Socialmedicinsk tidskrift, 2013)
This study describes the early development of specialized palliative home care in Sweden. Examples from northern Sweden are presented where the catchment areas extend beyond 30 minutes travelling time. The key elements in sparsely populated areas are collaboration with local district nurses and general practitioners and proactive planning for emergencies that may occur. These plans include informative dialogue with patients, their families, as well as locally involved staff. The challenge for specialized palliative medicine is to be available to everyone in need regardless of distances, site of care, and diagnosis.